“What’s past is prologue”: negotiating the authority of tense in reviewing Shakespeare - Kirwan, Peter (Taylor and Francis, 2010)
This paper, rooted in reviewing practice, engages with a little-discussed practical aspect of reviewing: the tense in which a theatre review is written. Noting that journalistic reviews use the present tense, whereas academic reviews use the past, this paper asks when a review moves into the past, and what implications the use of tense has for the review. The paper contends that the two tenses confer different kinds of authority on a review, which in turn have implications for positioning the object of review and the reviewer in relation to one another. Distinctions are made between reviewing a production or a single performance; between reviewing as a promise or as an archive; and between the omnipotent narrator and subjective spectator. The paper concludes that, in an age of increasingly cheap opinion, the past tense may be appropriated as a means for professional reviewers in all disciplines to consolidate the specificity of their reviewing authority.